Development of a Digital Droplet Polymerase Chain Reaction (ddPCR) assay to detect Leishmania DNA in samples from Cutaneous Leishmaniasis patients. (February 2019) - Ramírez, Juan David; Herrera, Giovanny; Muskus, Carlos; Mendez, Claudia; Duque, María Clara; Butcher, Robert
Highlights: ddPCR for Leishmania was developed and tested. ddPCR was acceptable for research purposes. qPCR performed better than ddPCR for Leishmania detection. Abstract: Aim: Here, we evaluate the ddPCR platform using an evaluated qPCR-based diagnostic assay for the detection of Leishmania infection in Cutaneous Leishmaniasis patients. Methods: A standard curve of cultured Leishmania parasite material and clinical samples of CL patients were tested with ddPCR to determine the analytical and diagnostic performance. Results: The limit of detection of the assay on the ddPCR platform was much higher than the published limit of detection of the same assay on the qPCR platform (100 vs 1 parasites/mL, respectively). Conclusion: While the performance of this assay in ddPCR format was acceptable for research purposes, it is not sufficient for clinical diagnostic purposes. The assay is more suited to the qPCR platform.